Efeito da velocidade ascensional na produção de hidrogênio em reator anaeróbio de leito fluidizado - Reis, Cristiane Marques dos (2010)
This study evaluated the influence of the upflow velocity in anaerobic fluidized bed reactor to produce hydrogen. In order to compare that effect, four reactors were used under different upflow velocities each: 0.30; 0.60; 1.24 and 1.88 cm.s-1. Expanded clay was used as support material for immobilization. A synthetic wastewater containing glucose (5000 mg.L-1) was used as substrate. Reactor R124 that was operated under minimum fluidization velocity (1.24 cm.s-1) showed the best values for hydrogen production. The maximum hydrogen production rate was found to be 1.22 L.h-1.L-1. The maximum hydrogen yield was 2.55 mol H2 mol-1 glucose and the biogas content ranged between 30,5 and 61,8 %. No methane was generated. The optimum TDH for expanded bed reactors was 1h while in fluidized bed reactors were 2h. Ethanol was the main metabolite produced, suggesting an ethanol-type fermentation. No trends were shown regardless of the upflow velocity imposed to the system. However, the higher the velocity applied, the higher the hydrogen production rate.